2011
DOI: 10.1080/17588928.2011.604717
|View full text |Cite
|
Sign up to set email alerts
|

On the functional anatomy of the urge-for-action

Abstract: Several common neuropsychiatric disorders (e.g., obsessive-compulsive disorder, Tourette syndrome (TS), autistic spectrum disorder) are associated with unpleasant bodily sensations that are perceived as an urge for action. Similarly, many of our everyday behaviors are also characterized by bodily sensations that we experience as urges for action. Where do these urges originate? In this paper, we consider the nature and the functional anatomy of "urges-for-action," both in the context of everyday behaviors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(155 citation statements)
references
References 83 publications
10
143
2
Order By: Relevance
“…Interestingly, a functional MRI (fMRI) study, which addressed the question of brain activations 2 s prior to tic onset in GTS patients and reported premonitory urges, revealed a distinct network of cortical areas involving the supplementary motor area, the insula, the parietal operculum and the anterior cingulate cortex, mainly active prior rather than at tic onset 27. Furthermore, a recent meta-analysis on fMRI studies addressing the question of urges preceding actions has proposed an anterior insular–cingulate motor area—mid insular loop, as a functional model of urges to act 28. Finally, structural MRI studies suggested that the primary somatosensory cortex plays an important role in GTS pathology29 30 with volumetric changes correlating with urge severity 29…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a functional MRI (fMRI) study, which addressed the question of brain activations 2 s prior to tic onset in GTS patients and reported premonitory urges, revealed a distinct network of cortical areas involving the supplementary motor area, the insula, the parietal operculum and the anterior cingulate cortex, mainly active prior rather than at tic onset 27. Furthermore, a recent meta-analysis on fMRI studies addressing the question of urges preceding actions has proposed an anterior insular–cingulate motor area—mid insular loop, as a functional model of urges to act 28. Finally, structural MRI studies suggested that the primary somatosensory cortex plays an important role in GTS pathology29 30 with volumetric changes correlating with urge severity 29…”
Section: Discussionmentioning
confidence: 99%
“…In a healthy state, prediction errors can activate the caudate [65], and then the caudate can activate urge-to-react [66].…”
Section: Dys-regulation Of the Agir Modelmentioning
confidence: 99%
“…Of note, these regions are also linked to the processing of (and awareness of) interoceptive bodily signals, including pain, cardiovascular activity, and hunger (9,10). These internal signals are motivationally salient, and thus their representation may correspondingly engender an urge for action (11)-that is, scratching in the case of itch. The planning of scratching movements is linked to premotor activity, whereas the intention to scratch (or not) is linked to engagement of the prefrontal cortex (12), consistent with this area's recognized role in willed actions (13).…”
mentioning
confidence: 99%